FERMI/LARGE AREA TELESCOPE DISCOVERY OF GAMMA-RAY EMISSION FROM THE FLAT-SPECTRUM RADIO QUASAR PKS 1454-354 - Abdo, A. A.; Ackermann, Markus; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2009)
We report the discovery by the Large Area Telescope (LAT) onboard the Fermi Gamma-Ray Space Telescope of high-energy gamma-ray (GeV) emission from the flat-spectrum radio quasar PKS 1454-354 (z = 1.424). On 2008 September 4, the source rose to a peak flux of (3.5 +/- 0.7) x 10(-6) ph cm(-2) s(-1) (E > 100 MeV) on a timescale of hours and then slowly dropped over the following 2 days. No significant spectral changes occurred during the flare. Fermi/LAT observations also showed that PKS 1454-354 is the most probable counterpart of the unidentified EGRET source 3EG J1500-3509. Multiwavelength measurements performed during the following days (7 September with Swift; 6-7 September with the ground-based optical telescope Automated Telescope for Optical Monitoring; 13 September with the Australia Telescope Compact Array) resulted in radio, optical, UV, and X-ray fluxes greater than archival data, confirming the activity of PKS 1454-354.
CRIS-Team WoS Importer:2020-01-15